Pola Komunikasi Mahasiswa dalam Penggunaan Smartphone (Studi pada Mahasiswa Marketing Communication Fek Binus University) - Rosidah, Rosidah; Herawati, Erni (Bina Nusantara University, 2013)
This research aimed to identify and know the pattern of smartphone usage among university students and pattern of communication they are doing with the smartphone. Quantitative research was used in this study, with descriptive design. Survey was conducted as data collecting method by distributing questionnaires to students of Marketing Communication (Marcomm) department, Faculty of Economic and Communication (FEK), Binus University. As a result, there were 134 questionnaires that can be proceed for data analysis. Sampling technique used in the research was simple random sampling. Since the research used descriptive design, thus the data analysis technique was descriptive statistics. The research is only limited to study the pattern of smartphone usage and pattern of communication among students of Marcomm department, FEK, Binus University, with their smartphone. Given the fact that smartphone has changed people’s behavior in communicating with others, it can be useful for example in developing appealing learning plan in education field, especially for youth. The function of mobile phone has undergone a rapid change with the existence of smartphone. With smartphone, one cannot only perform the traditional types of communication (phone or sms), but also go beyond that. This is due to the features provided by the smartphone which indeed accommodate the person’s needs to communicate each other more than just phone calls. Additionally, with the presence of Internet which has made the smartphone becoming inseparable with human’s life, since it integrates all medium and activities of communication into a single gadget. Smartphone has been proved to change the people’s habit in communicating each other and caused people’s dependency on the presence of this medium.